A STUDY ON ENGLISH STUDY PROGRAM STUDENTS’ PERCEPTIONS IN USING WHATSAPP APPLICATION AS A MOBILE-ASSISTED LANGUAGE LEARNING (MALL) TOOL - Rhena Fahreni; Rumiri Aruan; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The goal of this study is to identify the students' perceptions in using theWhatsApp application as a Mobile-Assisted Language Learning. To collect the data,this survey research used an online survey, then analyzed descriptively. Thequestionnaire in the survey used Technology Acceptance Model (TAM) with threeindicators to measure the students' perceptions. The survey was distributed to studentsfrom class C of batch 2019 of the English Study Program of Universitas Riau by usingcluster random sampling. 41 respondents answered the survey using Google Forms.The results were Perceived usefulness (70,97%) is in the very good category, PerceivedEase of Use (87,85%) is in the excellent category, and Behavioral Intention (78,28%) isin the very good. The result shows that the level of the students' perceptions in usingWhatsApp as a Mobile-Assisted Language Learning, in general, is Very Good(79,03%). Perceived Ease of Use was the indicator with the highest percentage(87,85%) which explains that students use WhatsApp easily. This research suggests thelecturer use WhatsApp as an application in the Mobile-Assisted Language Learning(MALL) tool.Key Words: Perception, WhatsApp, Mobile-Assisted Language Learning (MALL).